ChemInform Abstract: Large Negative Thermal Expansion and Anomalous Behavior on Compression in Cubic ReO3‐Type AIIBIVF6: CaZrF6 and CaHfF6. Issue 31 (August 2015) - Hancock, Justin C.; Chapman, Karena W.; Halder, Gregory J.; Morelock, Cody R.; Kaplan, Benjamin S.; Gallington, Leighanne C.; Bongiorno, Angelo; Han, Chu; Zhou, Si; Wilkinson, Angus P.
Abstract CaZrF6 (I), CaHfF6 (II), and CoZrF6 (III) are prepared by solid state reaction of CaF2 (CoF2) and ZrF4 (HfF4) in equimolar amounts (Cu or Ni tube in evacuated quartz tubes, 750 °C (I) or 850 °C (II, III), 24 h).